Pengaruh Kepemilikan Manajerial, Kinerja Keuangan, dan Kualitas Audit terhadap Kecurangan Laporan Keuangan - Oryza Alifia Khomariah; Khomsiyah Khomsiyah (Owner : Riset dan Jurnal Akuntansi, 2023)
Fraudulent financial reporting can be detrimental to various parties. Therefore, it is essential to identify the factors that can cause fraudulent financial reporting to prevent its occurrence. This study aims to investigate and evaluate how managerial ownership, financial performance, and audit quality affect fraudulent financial reporting. This research used secondary data from company financial and annual reports. Sample used in this study were companies in the consumer goods manufacturing sector listed on the Indonesia Stock Exchange (IDX) between 2019 and 2021. Multiple linear regression analysis and purposive sampling method with 134 samples covering the 2019–2021 period was employed in this research. This study shows that financial performance proxied by leverage and profitability ratio, managerial ownership, and audit quality does not affect fraudulent financial reporting, while financial performance proxied by the liquidity ratios has negative affect towards fraudulent financial reporting